Parental Image in the Perception of Children from Divorced Marriages in Qualitative Research - Pietkiewicz-Pareek, Beata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The issue of the family and its dysfunctions has been at the centre of interest of various social sciences for many years, despite the fact that it is an extremely difficult subject to study. The phenomenon of divorce is rarely presented from the point of view of children. Hence, the aim of this research was to unveil this cognitive perspective and to determine the image of parents in the perception of children from divorced families. The key task concerned how a child in a divorced family perceives herself or himself and other family members. Fritz Schutze’s method of narrative interview analysis was used inthe study.
Keywords: children; divorce; family structure disruptions; single-parent family